Sport Sciences Full Professors` assessment about the main aspects inside the Spanish faculty evaluation - Jesús Salado Tarodo; Enrique Ortega Toro; Pedro Sáenz-López Buñuel (Federación Extremeña de Balonmano; University of Extremadura, 2023)
This study aims to know the Spanish Physical Activity and Sport Sciences Full Professors` opinion about Spanish National Habilitation and Evaluation Agency´s faculty evaluation. The sample was composed of 17 full professors. The instrument used was a semi-structured interview. The qualitative analysis of the data obtained from the interviews indicates that in opinion of the Spanish physical activity and sport sciences full professors teaching and researching should have the same importance for the faculty evaluation. In addition, it is important to underline the need to improve and objectify both researching and teaching evaluation introducing for example qualitative evaluations of faculty's scientific productions.